The Implementation of Islamic Education in Building Preprimary Disabled Students Character - Edi Sutejo; Nurdin Nurdin; Ahmad Syahid (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2021)
This study examined the implementation of Islamic education in building preprimary disabled students characters. The main focus of this study was teachers strategies in building characters for mentally retarded children in the subject of Islamic religious education and character. In conducting the study, we used a qualitative case study method. The case of this study was a state disabled in Palu city. Data were gathered through direct field observation, in-depth interviews which involve teachers and the school principla. We also analyzed written material, such as the school teaching activities, to understand how the character building strategies were integrated in the disabled school curriculum. Our study found that the teacher's strategies in building character of mentally retarded children in the subject of Islamic Religious Education were through habituation and modeling techniques. The teachers of Islamic religious education applied learning habits that contain good values ​​and attitudes. This included familiarizing with habits to maintaining cleanliness, Quran recitation, practicing prayers, and getting used to giving donation.